PERAN KOMUNIKASI EFEKTIF DALAM KEPEMIMPINAN DEMOKRATIS DI SMK SCIENCE TECHNOLOGY AND BUSINESS (STB) SAWANGAN - Sapto Hadi Imambachri; Turkamun Turkamun; Deni Darmawan; Edi Junaedi; Ismul Bathni Sumadikarta (Universiitas Pamulang, 2021)
ABSTRACT Various studies have been carried out aimed at knowing effective communication models and leadership models in an organization. Bartol (2008: 505) states that